Analisis Komparatif Capaian Pembelajaran Biologi: Studi Diferensiasi Antara Siswa Pengguna Aktif Game Online Dan Non Pengguna Di SMA Negeri 1 Garut: (Comparative Analysis Of Biology Learning Achievement: A Study Of Differentiation Between Active Online Game Users And Non-Users At State SMA Negeri 1 Garut) - Wildani, Sahrul; Hernawati, Dewi; Putri, Diah Ika (BIODIK, 2026)
The phenomenon of online gaming among students often gives rise to negative stigma regarding declining academic performance. This study aims to empirically test whether there is a significant difference (differentiation) in learning outcomes between students who actively play online games and those who do not. Using a comparative quantitative approach with an ex-post facto design, this study involved 44 students as samples selected through purposive sampling, consisting of 27 students in the active player category (Gamers) and 17 students in the non-player category (non-Gamers). Learning outcome data were collected through report card documentation and analyzed using the Independent Sample t-test statistical test with the help of SPSS. The test results showed that the average (mean) score for the group of gamers was 84.06, while that for the group of non-gamers was 84.53, with a very slight difference (0.47 points). Based on the t-test, a significance value (Sig. 2-tailed) of 0.474 (p > 0.05) was obtained. These findings confirm that the Null Hypothesis (H0) is accepted, which means that there is no statistically significant difference in the learning outcomes of the two groups. This study concludes that online gaming activity is not the sole predictor of a decline in student achievement. This indicates that there is a factor of good self-regulation among students who play games in balancing their hobbies and academic obligations. Abstrak. Fenomena game online di kalangan pelajar sering kali memunculkan stigma negatif terkait penurunan performa akademik. Penelitian ini bertujuan untuk menguji secara empiris apakah terdapat perbedaan signifikan (diferensiasi) pada capaian pembelajaran antara siswa yang aktif bermain game online dengan siswa yang tidak bermain game online. Menggunakan pendekatan kuantitatif komparatif dengan desain ex-post facto, penelitian ini melibatkan 44 siswa sebagai sampel yang dipilih melalui teknik purposive sampling, terdiri dari 27 siswa kategori pemain aktif (Gamer) dan 17 siswa kategori non-pemain (non-Gamer). Data hasil belajar dikumpulkan melalui dokumentasi nilai rapor dan dianalisis menggunakan uji statistik Independent Sample t-test dengan bantuan SPSS. Hasil pengujian menunjukkan nilai rata-rata (mean) kelompok pemain game sebesar 84,06, sedangkan kelompok non-pemain sebesar 84,53, dengan selisih yang sangat tipis (0,47 poin). Berdasarkan uji t, diperoleh nilai signifikansi (Sig. 2-tailed) sebesar 0,474 (p > 0,05). Temuan ini mengonfirmasi bahwa Hipotesis Nol (H0) diterima, yang berarti tidak terdapat perbedaan yang signifikan secara statistik pada hasil belajar kedua kelompok tersebut. Penelitian ini menyimpulkan bahwa aktivitas bermain game online tidak  menjadi prediktor tunggal turunnya prestasi siswa. Hal ini mengindikasikan adanya faktor manajemen diri (self-regulation) yang baik pada siswa pemain Game dalam menyeimbangkan hobi dan kewajiban akademiknya.